An Analysis of Speech Acts Used in English Teaching - Nur Indah Sari (Borneo Educational Journal (Borju), 2019)
This study focused on analyzing speech acts and their forces performed by the English teacher in EF (English First) Samarinda. This study is a descriptive study using a qualitative approach. There are two teachers as the subjects of the data. The data of the study are the utterances performed by the English teachers. The main instrument of the study is the researcher herself with the help of an audio-video recorder during the data collection. In this study, the researcher uses Searle’s theory about types of speech acts. The findings show that 1) there are four kinds of speech acts performed by the teacher during the teaching and learning process, those were representative, commissive, directive, and expressive, 2) the most frequently speech act performed by the teachers is directive speech act while the least speech act performed is commissive. The directive speech act occurs as the most speech act performed by the teacher because they want the students to be more active and can contribute more during the teaching and learning process.